A study on the morphology and taxonomy of the males of two Dactylopius species (Hemiptera : Coccoidea) - Loubser, H. J. M.(Hendrik Johannes Michiel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1966.